LINGUISTIC AND RHETORICAL FEATURES OF EFFECTIVE TEACHER COMMUNICATION - Djurayeva Ranokhon (Ustozlar uchun, 2025)
Abstract Effective communication is an essential component of successful teaching and learning. This paper explores the linguistic and rhetorical features that define effective teacher communication, focusing on the dynamic interaction between teachers and students in diverse educational contexts. Through an interdisciplinary approach that integrates insights from linguistics, rhetoric, education, and cognitive psychology, the study identifies key strategies that enhance clarity, engagement, and understanding in classroom discourse. Particular attention is given to language structure, rhetorical moves, pragmatic competence, and the socio-cultural dimensions of teacher talk.